Experimental study on shear behavior of steel plates with different artificial corrosion positions. (June 2021) - Sun, Qingwei; Gao, Youran; Zhao, Zhongwei; Zheng, Yajie
Abstract: Herein, 11 artificially corroded steel plates and one intact steel plate specimen were designed to study the influence of corrosion on steel plates on the degradation of their shear capacity. The shear capacity of corroded steel plates was experimentally investigated. Furthermore, the shear performance of corroded plates, including their critical shear load and shear capacity, was evaluated. In addition, the influence of the location of pitting, shape of pitting, and the degree of pitting on the degradation of the shear capacity was discussed and variations in the regular pattern of the tension field of corroded steel plate specimens were investigated. Test results show that the location pitting was primarily responsible for the degradation of the shear capacity, yield load, and critical shear load. Moreover, the degradation degree of the shear capacity in the direction of the pressure band was observed to be greater than that in the direction of the tension field. Results also show that the shear capacity of specimens decreased with increasing pitting corrosion distribution. The shear capacity of the specimen with the largest corrosion distribution decreased to 42% of that of the intact plate. Compared with the uncorroded specimen, the angle and width of the tensile band were greatly affected by the corrosion area. This study provides reference data for evaluating the degradation degree of the shear capacity of corroded steel plate.